German-Turkish Perspectives on IT and Innovation Management Challenges and Approaches (International Series,, 2018)
This book includes papers presented at the 2nd Economic forum: German-Turkish perspectives on IT and Innovation Management at the FOM in Munich, organized by the FOM University of Applied Sciences and Atatürk University Erzurum. Patron of the conference was Prof. Dr. Johanna Wanka, Federal Minister for Education and Research. To mark the German-Turkish year of science, both countries picked out global and societal challenges as a central theme and explored solution strategies as well as their implementation in new technologies and innovations. The papers discuss the effects of new technologies and innovations from different perspectives - from IT management, banking and finance to the special challenges of SMEs. The Editors Fehim Bakırcı is a professor of ecomomic theory and labor economy at the Faculty of Economics and Administrative Sciences and head of the Department of International Trade and Logistic at Atatürk University in Erzurum, Turkey. His research fields are micro economy, labor economy, industrial economy and efficiency and economic productivity. Thomas Heupel studied economics at the University of Siegen and subsequently worked as a research assistant at the IöB (Institut für ökologische Betriebswirtschaft) and managing director of the SMI (Siegener Mittelstandsinstitut) at the University of Siegen, Germany. He is a professor of business administration, with a focus on cost accounting and controlling. Since 2009 he has been vice rector of research at the FOM University of Applied Sciences in Essen, Germany. His research focuses on the fields of behavioural economics, automotive industry management, demographic change, blue ocean strategy, management of SMEs and cost control. He is a member of several scientific institutions' advisory boards and editor of numerous academic books. Orhan Kocagöz studied business administration at the Friedrich Alexander University in Erlangen and received a doctorate on the topic "Business groups in developing countries. The rise, organization and business policy of Turkish holdings". Since 2011 he has been professor of general business administration in particular international management at the FOM University of Applied Sciences in Nuremberg, Germany. Üstün Özen is professor at the Faculty of Economics and Administrative Sciences and head of the Department of Management Information Systems at the Atatürk University in Erzurum, Turkey. He has published a wide spectrum of articles in various national and international journals in the fields of information systems management, project management, system analysis & design, distance learning, and e-commerce, as well as numerous books. He has also presented a number of scientific papers at national and international symposiums.